PENGARUH EDUKASI MEDIA VIDEO TERHADAP PENGETAHUAN TENTANG AKTIVITAS FISIK BAGI PENGGUNA SOCIAL MEDIA INSTAGRAM - Martani - Maharani; Mohammad Zainol Rachman; Budi Suharno (Jurnal Pendidikan Kesehatan, 2021)
Physical activity is an activity carried out in a physical and healthy condition based on the ability of the individual body. Based on a preliminary study of the phenomenon for respondents who perform the physical activity but still do not know enough about physical activity. This research uses pre experimental quantitative research with the one group pretest posttest method. The population in this study is followers of social media Instagram researchers, as many as 38. The technique of placing the sample in this research is systematic sampling and purposive sampling. The research was conducted online from September 2020 until April 2021. Data analysis was processed using the Wilcoxon signed rank test. The results showed that the Wilcoxon test was the Z value equal negative 4.023, at the 5 percent significance level with the p asymp value Sig. 2 tailed of 0.000. 0,000 points less than 0.05, hence it states that ha is accepted, meaning that there is a comparison during pretest and posttest. It might say that this research has the effect of education through video media on knowledge of physical activity for Instagram social media users.